(untitled) (Materiali di Estetica. Terza serie, 2020)
Calvino’s posthumous collection of tales, The five senses, is analyzed with an emphasis on closeness to European epistemological and philosophical experiences. The little system of the short stories is related to Michel Serres book “Les cinq sens” (1985): We don’t know if Calvino read it, but the topics addressed in this essay, namely the complexity of sensitive experience and the epistemology of living beings, belong to a cultural environment familiar to Calvino.